2008
DOI: 10.1002/psc.1075
|View full text |Cite
|
Sign up to set email alerts
|

Selenopeptide chemistry

Abstract: This review focuses on the chemical aspects of the 21st proteinogenic amino acid, selenocysteine in peptides and proteins. It describes the physicochemical properties of selenium/sulfur and selenocysteine/cysteine based on comprehensive structural (X-ray, NMR, CD) and biological data, and illustrates why selenocysteine is considered the most conservative substitution of cysteine. The main focus lies on the synthetic methods on selenocysteine incorporation into peptides and proteins, including an overview of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
150
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 145 publications
(154 citation statements)
references
References 142 publications
4
150
0
Order By: Relevance
“…For example, substitution of S-S bonds by isosteric Se-Se bonds can improve peptide folding and stability [25][26][27] . We envisaged that replacement of a disulphide bond (S-S, bond length 2.03 Å) 28 by a nonreducible selenocystathionine (SeCtt) bond (Se-C, bond length 1.95-1.99 Å) 28 might enhance the metabolic stability of cyclic peptides with minimal structural perturbation. Furthermore, the low pK a of the selenol in Sec 29 should allow selenide ring closure 1 to proceed efficiently under acidic to neutral conditions, largely preventing deterioration of labile electrophilic moieties at higher pH (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For example, substitution of S-S bonds by isosteric Se-Se bonds can improve peptide folding and stability [25][26][27] . We envisaged that replacement of a disulphide bond (S-S, bond length 2.03 Å) 28 by a nonreducible selenocystathionine (SeCtt) bond (Se-C, bond length 1.95-1.99 Å) 28 might enhance the metabolic stability of cyclic peptides with minimal structural perturbation. Furthermore, the low pK a of the selenol in Sec 29 should allow selenide ring closure 1 to proceed efficiently under acidic to neutral conditions, largely preventing deterioration of labile electrophilic moieties at higher pH (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…If the role of the vicinal disulfide moiety were purely structural, replacing the vicinal disulfide bond with bioisosteric groups that mimic the vicinal disulfide moiety would be expected to have little effect on KOR activity. Selenium has very similar physicochemical properties as sulfur, 73 and it has been shown that diseleno and seleno-sulfur bridges can be used to replace disulfide bridges without affecting structure. 74 The synthesized selenocysteine analogues 52 and 53 had similar KOR affinity compared to their disulfide analogues 26−35, supporting the importance of the vicinal disulfide moiety as a structural contributor of the pharmacophore.…”
Section: Journal Of Medicinal Chemistrymentioning
confidence: 99%
“…9 Therefore, preparation of recombinant selenopeptides by site-directed mutagenesis applying molecular biology technology is still not easy. 10 In the meantime, a conventional method for the chemical synthesis of selenopeptides 11 is advantageous because it allows sequential introduction of a variety of amino acids, including non-natural amino acids, with an arbitrary order to a growing peptide chain based only on chemical reaction processes. Accordingly, the chemical methods, most frequently a solid-phase peptide synthesis (SPPS) method, have been applied for the synthesis of various selenopeptides.…”
Section: Introductionmentioning
confidence: 99%